Pengembangan Media Pembelajaran PowerPoint Interaktif Pengetahuan Peralatan Dapur dan Bahan Makanan di SMKN 2 Tejakula - Sari, Kadek Lany Widya; Sukerti, Ni Wayan; Masdarini, Luh (Universitas Mathla'ul Anwar Banten, 2025)
This study aims to describe the development of interactive PowerPoint on the sub-learning material of Kitchen Equipment and Food Ingredients at SMK Negeri 2 Tejakula. This research is an R & D (Research and Development) with 4D development model (Define, Design, Develop, Disseminate). The subjects of this study involved learning material experts, learning media experts, learning design experts, and 20 students of the Culinary Department at SMK Negeri 2 Tejakula for the small group testing. The data collection method used was Likert scale scoring questionnaire. The data were then analyzed using quantitative descriptive techniques. The results of this study are as follows: Interactive PowerPoint learning media has been developed through four stages, namely; (1) define, which is the stage of analyzing the learning material based on the Learning Outcomes (CP) and Learning Objectives (ATP); (2) design, which is the stage of designing material and making interactive PowerPoint products; (3) development, is the stage of validity testing by experts with a trial score of 96.39% from material experts, 94.62% from media experts, and 95.00% from learning design experts, all of which are classified as